Facing Digital Transformation in The Media Industry: Challenges and Opportunities - Lusiana, Dewi; Parastry, Annisa (Golden Ratio of Community Services and Dedication, 2025)
Digital transformation in the media industry has significantly changed how information is produced, disseminated, and consumed by the public. This community service activity was conducted in East Belitung Regency, involving local journalists and reporters as the primary participants. The activity aimed to raise awareness and enhance the capacity of journalists to face the challenges and seize the opportunities of the digital era. The materials covered the importance of adapting to technology, utilizing digital platforms, building personal branding, and maintaining journalistic integrity and ethics amidst the fast-paced information flow. The results showed that although there are still obstacles in adopting technology, participants began to understand the importance of mastering digital media to sustain journalism. This activity highlighted that journalists not only need to respond to change but can also actively shape a more inclusive, credible, and meaningful future for journalism in the digital age.